Ethanolysis Pretreatment of Crude Palm Oil in High Shear Reactor - Hidrotunnisa, Hidrotunnisa; Yanti, Rini; Hidayat, Chusnul (agriTECH, 2025)
Crude palm oil (CPO) is characterized by high carotenoid content, dissolving in the oil system and causing a difficult extraction process. To overcome this problem, transesterification of CPO with ethanol was performed to improve the carotenoid extractability using sodium hydroxide as a catalyst. Therefore, this study aimed to investigate the effect of ethanolysis parameters on the carotenoid and fatty acid ethyl ester (FAEE) content of CPO. FAEE content was quantified by thin-layer chromatography and total carotenoid content (TCC) was determined through a UV-Vis spectrophotometer. Reaction time (15-150 min), catalyst concentration (0.65-3.25%), reaction temperature (3070 ℃), and stirring speed (500-2000 rpm) were determined by one factor at a time (OFAT) design. The results showed that ethanolysis time and temperature did not affect TCC along the study range, while ethanolysis time of 45 minutes and temperature of 70 ℃ increased FAEE content. Additionally, catalyst concentration of 1.95% and stirring speed at 2000 rpm increased TCC and FAEE. The best ethanolysis parameters were obtained at 45 minutes, the temperature of 50 ℃, catalyst concentration of 1.3%, and stirring speed of 2000 rpm, yielding FAEE 1358±16 ppm and TCC 99.9±0.2%. This showed that ethanolysis produced high FAEE content and improved carotenoids in the oil system.